2018
DOI: 10.1002/ejoc.201800249
|View full text |Cite
|
Sign up to set email alerts
|

POCl3‐Promoted Trifluoromethylthiolation‐Based Vicinal Bifunctionalization of Indoles with CF3SO2Na

Abstract: An efficient trifluoromethylthiolation‐based vicinal bifunctionalization of indoles with sodium trifluoromethanesulfinate in the presence of phosphorus oxychloride were achieved to introduce a chlorine atom into the 2‐position under transition‐metal‐free and mild conditions. The protocol could also extend to other sodium perfluoroalkanesulfinates or phosphorus oxybromide. The possible pathway was proposed based on the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 60 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…The structure of bifunctionalized product 7 d was confirmed by single‐crystal X‐ray analysis. Very recently, the Liu group reported a similar transformation using POCl 3 as the chlorination reagent . We attempted to gain some insights into the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of bifunctionalized product 7 d was confirmed by single‐crystal X‐ray analysis. Very recently, the Liu group reported a similar transformation using POCl 3 as the chlorination reagent . We attempted to gain some insights into the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently,t he Liu group reported as imilart ransformation using POCl 3 as the chlorination reagent. [28] We attempted to gain some insights into the reaction mechanism. 19 FNMR analysiso ft his reaction process showedt hat 4a is an intermediate piror to the chlorotrifluoromethylthiolated product 7a,w hich meanst hat 7a was formed by chlorination of 4a.T o gain more insights, especially for the chlorination of 4a,s everal control experiments were conducted (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Since Zhang's group first reported the use of sodium trifluoromethanesulfinate in copper‐catalyzed trifluoromethylthiolation reaction of indoles, transition metal‐free electrophilic trifluoromethylthiolation reactions with the CF 3 SO 2 Na/[P] or CF 3 SO 2 Cl/[P] reagent system have been successively developed by Cai's, Lu's and our group . Recently, we reported an efficient trifluoromethylthiolation‐based vicinal bifunctionalization of indoles using CF 3 SO 2 Na/POX 3 system, in which a halogen atom was introduced into the 2‐position at the same time under mild conditions, and Zhang et al. reported the trifluoromethylthiolation of ketones with CF 3 SOCl [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Controle xperiments indicated that base was important for the reaction (entry 7). So we studied the base effect further.However,v arious organic bases, such as triethylamine (Et 3 N), triisopropylamine (iPr 3 N), N-methylpiperidine andp iperidine,c ould not improvet he yield of 2a (entries 8-11), and inorganic bases (Na 2 CO 3 ,K 2 CO 3 ,N aHCO 3 , NaOH, K 3 PO 4 )f ailed to promote this bifunctionalization reaction with full recovery of 1a (entries [12][13][14][15][16]. Therefore, pyridine was chosen as the base to further study the solvent effect.…”
mentioning
confidence: 99%
“…Since 2011, S 8 , 11 CS 2 , 12 KSCN, 13 DMSO, 14 NaS 2 O 3 , 15 thiourea, 16 Bunte salts, 17 potassium O-ethyl dithiocarbonate, 18 and N-(aryl/alkylsulfanyl)succinimides, 19 etc., have all been employed as sulfur sources for the synthesis of sulfides, however, most of these sources provide only a single sulfur atom. Sulfur sources, such as thiols, 20,21 disulfides, 22 sulfonyl chlorides, 10,20, and sodium sulfinates 25,29,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and sulfonyl hydrazides have also been employed in the synthesis of sulfides, with the desired products being obtained in good yields. These protocols greatly enrich existing synthetic routes, and they may provide an alternative to traditionally used methodologies in some cases.…”
Section: Introductionmentioning
confidence: 99%